A Direct Method for the Analyticity of the Pressure for Certain Classical Unbounded Models. (13th February 2011) - Lo, Assane
Abstract : The goal of this paper is to provide estimates leading to a direct proof of the analyticity of the pressure for certain classical unbounded models. We use our new formula (Lo, 2007) to establish the analyticity of the pressure in the thermodynamic limit for a wide class of classical unbounded models in statistical mechanics.